Southern Bantu origins: light from kinship terminology - Hammond-Tooke, W. D. (Southern African Humanities, 2021)
Evidence from archaeology and linguistics suggests that ancestors of Nguni and Sotho-Tswana speakers came from East Africa and had spread south of the Limpopo river by about AD 1350. These Southern Bantu groups possess the Iroquois classificatory kinship system in which a single genderless term derived from the verb 'to beget' is applied to cross-cousins - the children of father's sister and mother's brother. This system makes cross-cousin marriage possible. The Iroquois system also occurs in groups of Murdock's Equatorial, Interlacustrine, Tanganyika and Central Bantu provinces. Following Murdock's suggestion that kinship may provide clues to linguistic affiliation and migrations, I examine the occurrence of a limited range of cultural attributes in Bantu speaking groups with the Iroquois system. This reveals strong similarities between Interlacustrine Bantu groups and the Nguni on the one hand, and between Tanzanian groups and Sotho speakers on the other. The ethnographic evidence therefore supports East Africa as the place of origin of Nguni and Sotho speakers. To cite this article: Hammond-Tooke, W.D. 2004. Southern Bantu origins: light from kinship terminology. Southern African Humanities 16: 71-8.